Curricular design for the construction of a peace culture - González, Raiza; Zabala, Carmen; Berruela, Hercilia (Avances en Supervisión Educativa, 2009)
This investigation had as purpose from the analysis of the contributions of sciences of the conduct, pedagogical and spiritual, to apply a curricular design for the development of competitions  in the educational one like mediator of a culture of peace in the classroom. study was descriptive, of action-reflection-intervention in the modality of study of case with application of tests you diagnose, observation log, shootings, psicoterapéuticas interviews, techniques and factories, considering the analysis units: documents and   students. The population was represented by the students of the Elective I: mention Sciences and Technology of the Education. The results revealed that educational as mediating of a peace culture must demonstrate competitions of knowing, doing, to coexist and to be; in the field of the Neurolingüística; conflict mediation; familiar constellations; psiconeuroimunología; support psycotherapy; intelligence  interpersonal, emotional and naturista; abilities for the negotiation and cooperation; responsibility, respect, discipline, honesty, gratitude, coherence, empathy, spiritual development,  faith and nonviolence.
Keywords: program; competitions; educational culture of peace; curricular design